A simple stress correction method for explicit integration algorithm of elastoplastic constitutive models and its application to advanced anisotropic S-CLAY1 model - Wang, Hui; Li, Lin; Li, Jingpei; Sun, De'an (Computers and geotechnics, 2022)
[Display omitted] The stress correction, which prevents stresses drifting from the yield surface, is a key step in the explicit scheme for integrating elastoplastic constitutive models in finite element analyses. In this paper, a simple, robust, and efficient stress correction method is proposed for improving the well-established explicit modified Euler scheme of Sloan et al. (2001). The method subtly proposes a single correction coefficient assuming that the stress components are proportional to the corrected stress components on the yield surface. The expression of the correction coefficient can be explicitly determined with the current stress state and the yield function, which allows the correction procedure to be easily and conveniently accomplished through multiplying the stress components by a single coefficient without resorting to the Newton iteration algorithm. The proposed method is applied to develop a user defined material (UMAT) subroutine for the advanced anisotropic elastoplastic model S-CLAY1 (Wheeler et al. 2003), which is subsequently used to simulate triaxial tests, the collapse of a rigid smooth square footing and a natural ground under embankment loading. The comparisons with other stress correction methods, the exact results from MATLAB, and the field measured values demonstrate the stability, robust, efficiency and validity of the proposed method.